MAKKIYAH DAN MADANIYAH DALAM AL-QUR’AN - Khairil Gufron Mursyid; Mursyidatul Awaliyah (STIT Darul Hijrah Martapura, 2021)
This study adopts a qualitative approach of literature review with the deep-seated aim of understanding the various responses to the evolution and dynamics of the Quranic revelation process. The methodological process begins with data collection sourced from relevant literature, both classic and contemporary, which includes works of great scholars such as Abu al-Qasim al-Naisaburi in